Guidelines for designing highly concentrated electrolytes for low temperature applications. Issue 68 (27th July 2020) - Ah-lung, Guillaume; Flamme, Benjamin; Ghamouss, Fouad; Maréchal, Manuel; Jacquemin, Johan
Abstract : The WISS concept for the rational design of aqueous electrolytes for low temperature applications. Abstract : The redefinition of the commonly named "water-in-salt" clarifies the operating temperatures of the state-of-the-art LiTFSI-based aqueous solutions. An in-depth study shows its mismatch for low temperature applications. In contrast, the recommended strategy is to design an electrolyte with an invariant composition, as exemplified by the eutectic water/LiNO3 that is able to electrochemically cycle down to −23 °C.